Tanggungjawab Dewan Pengawas Syariah Terkait Pelanggaran Hukum pada Asuransi Syariah (Analisis Yuridis Terhadap Undang-undang Nomor 40 Tahun 2014 Tentang Perasuransian) - Cahaya Permata (TAQNIN: Jurnal Syariah dan Hukum, 2019)
Supervision of the implementation of sharia insurance is very necessary in order to provide maximum protection to all interested parties. Supervision of sharia insurance is the responsibility of the Sharia Supervisory Board (DPS). If there is a violation of law against sharia principles carried out by insurance companies, DPS should be legally responsible. DPS's duty is to supervise and provide advice and advice to managers of insurance companies to carry out their business activities in accordance with statutory provisions that regulate the basic principles of conducting insurance business with sharia principles, DSN MUI fatwas and other provisions related to the implementation of insurance business with sharia principles. DPS is only responsible if it ignores sharia principles violations carried out by sharia insurance companies. DPS can be subjected to administrative and even criminal sanctions for not carrying out their duties.